(3eMGVQGJ aj ebjGS GdeQGLYI hGdJObjb GdLHGFj (B: s (3ehLgI daGFOI SfI GdGhdi eGSJQ JNUU eMGSHI h JObjb (B/ s - (3dLfGa,YHO GdQRGbs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3eaGgje YGeI Mhd GdLHGjI GdbGfhf GdVQjHj bhGfjf GdGSJKeGQ h GdGeJjGR GdLHGFj eY GdGdeGe HeMJhi echfGJ GdfXGe GdVQjHj GdLRGFQj, GdGWGQ GdeaGgjej dYedjI GdeQGLYI GdLHGFjI , YdGbI GdeQGLYI GdLHGFjI HHGbj GdeQGLYGJ GdGNQi , CTcGd GdeQGLYI GdLHGFjI hab GdJTQjY GdLRGFQj, GdeQGLYI GdLHGFjI GdeYebI Ydi eMGSHI GdTQcGJ GdYQV GdfbOj h GdJWHjbGJ , GdJMbjb GdeYeb aj GdhVYjI GdLHGFjI GdTGedI ddecda GdYQV GdfXQj h GdJWHjbGJ , HGbj CfhGY GdeQGLYGJ GdLHGFjI GdCNQi GdYQV GdfXQj h GdJWHjbGJ(B.s
(3eQGLY U(B.161s
Keywords: (3GdVQGFHs